The formation of yttrium aluminium monoclinic (Y4Al2O9) by sol-gel synthesis at low heating temperature - Mohd Zawawi, Mohd Khairul Ikhwan; Azis, Raba'ah Syahidah; Hashim, Mansor; Holland, Diane; Howes, A. P.; Zakaria, Azmi; Hassan, Jumiah (Australian Ceramic Society, 2014)
Y4Al2O9 has been synthesized by means of the citrate-nitrate sol-gel combustion method using yttrium (III) nitrate and aluminium (III) nitrate. DTA/TG analysis, X-ray diffraction (XRD), FT-IR and 27Al magic angle spinning nuclear magnetic resonance (MAS NMR) measurements were used to characterize the phase decomposition, weight loss of the sample, the crystal structure and phase formation of the Y4Al2O9 material. XRD shows the Y4Al2O9 starts to crystallize at low temperature, 700°C, with an average particle size around 49 nm.